From full life to balanced life: Extending Martin Seligman's route to happiness - Aloys Prinz; Björn Bünger (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2009)
In this paper, a formalization of Martin Seligman's concept of full life is presented by employing basic microeconomics. With the formalized version of the concept, it can be explained why people differ with respect to the levels of pleasant, engaged and meaningful life they are trying to realize. Moreover, it is suggested to extend Seligman's concept of full life to the concept of balanced life. This extension requires that in addition to differences in people's preferences regarding aspects of life also differences in the time opportunity costs are to be taken into account. Finally, a scorecard-approach is proposed to track personal advancement in the process of life balancing.
Keywords: I31; D69; D11; 330; full life; happiness; allocation of time